Seasonal variability of CO2 system and air-sea fluxes on the east coast of Gran Canaria - Aldrich Rodríguez, Ariadna; González Dávila, Melchor; Santana Casiano, Magdalena; González González, Aridane (Servicio de Publicaciones y Difusión Científica de la Universidad de Las Palmas de Gran Canaria (ULPGC), 2023)
This study describes the annual pattern, from March 2020 to April 2021, of different parameters of the CO2 system and ocean acidification in the eastern coast of Gran Canaria Island (Gando Bay) via the monitoring of pHT, total dissolved inorganic carbon (CT), total alkalinity (AT) and CO2 fugacity (fCO2), as well as other parameters such as sea surface salinity and temperature (SSS and SST), dissolved oxygen (O2), chlorophyll (chl-a) and wind. In addition, the flux of CO2 (FCO2) between the atmosphere and the sea surface has been computed. The results show a clear seasonal fCO2 variation in seawater from 380 μatm (in winter) to 430 μatm (in summer), where the opposite behaviour was observed in pHT with a range of variation of 8.072 to 8.032 and CT between 2123.2 and 2101.5 μmol kg-1. The thermal/nonthermal processes (ratio T/NT) affect the seasonal fCO2 in seawater with a value of 1.38. The temperature mainly controls the variability of fCO2 in the region, but the non-thermal factors have a higher contribution than other studies in the open ocean. Results indicate a higher role of the primary production in the area, which reduces CT and the fCO2. In addition, the rise of a water mass with low salinity (36.4) and temperature (22 ºC) due to the effect of high and constant Trade Winds (July and August), contribute to the physical and chemical seasonal variability in the Bay. This water mass had also higher concentrations of CT due to the remineralization of organic matter that takes place at depth and out of the Bay. The calculated flux of CO2 at the buoy location was 0.27 ± 0.22 mmol m-2 d-1, showing a mean behaviour as a slight source of CO2. Assuming this value for all Gando Bay, it was found that the area emits 4.58 ± 3.68 Tons yr-1 of CO2 each year. This coastal time-series in the Canary Islands is contributing to improve our knowledge about the impacts of climate change in the CO2 system and ocean acidification in coastal systems, also, incrementing the data set for the global carbon budget. 361 360 2